Correlation between of hepatitis A virus infection and vitamin B12 level in Iraqi patients (Texas Journal of Agriculture and Biological Sciences, 2022)
Hepatitis A is a public health problem all over the world, especially in developing countries, because the virus is so common in the environment. Anti-HAV IgM antibodies were detected in the serum of 100 of the 120 persons (patients group) collected from the Al-Zahra hospital in Al-rusafa/Baghdad between November 2021 and March 2022. Twenty individuals with negative blood levels of anti-HAV IgM antibodies were deemed a control group. Anti-HAV IgM antibodies were significantly higher (P